2019
DOI: 10.14260/jemds/2019/615
|View full text |Cite
|
Sign up to set email alerts
|

Lip Print as a Method for Forensic Identification on Malaysian with Chinese Ethnicity

Abstract: BACKGROUND Forensic dentistry is a branch of forensic medicine that has now become a standalone science. Lip print is used to identify forensic and non-forensic cases. The aim of this research is to find the pattern of lip print based on Suzuki and Tsuchihashi classification according to quadrant, to investigate the difference of dominant lip print pattern in general and also according to the different gender (male and female) among Malaysians with Chinese ethnicity at University of Northern Sumatra. METHODS T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…One study 83 did not report which technique was used. In general, twenty-four studies (33%) 12 , 14 , 24 , 26 , 28 , 31 , 35 , 42 44 , 47 , 51 , 53 – 55 , 57 , 63 , 66 , 67 , 74 76 , 82 did not find evidence of difference of lip print patterns between males and females, while 67% 1 , 2 , 4 – 6 , 10 , 11 , 13 , 15 , 25 , 27 , 29 , 31 34 , 36 41 , 45 , 46 , 48 50 , 52 , 56 , 58 – 62 , 64 , 65 , 68 73 , 77 81 , 83 , 84 detected differences.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…One study 83 did not report which technique was used. In general, twenty-four studies (33%) 12 , 14 , 24 , 26 , 28 , 31 , 35 , 42 44 , 47 , 51 , 53 – 55 , 57 , 63 , 66 , 67 , 74 76 , 82 did not find evidence of difference of lip print patterns between males and females, while 67% 1 , 2 , 4 – 6 , 10 , 11 , 13 , 15 , 25 , 27 , 29 , 31 34 , 36 41 , 45 , 46 , 48 50 , 52 , 56 , 58 – 62 , 64 , 65 , 68 73 , 77 81 , 83 , 84 detected differences.…”
Section: Resultsmentioning
confidence: 86%
“…Six studies did not fulfill the inclusion criteria (Appendix 1), and full texts were not found for twenty studies, even after trying to contact the authors or libraries. Finally, a total of 72 studies were selected for qualitative analysis 1 , 2 , 4 – 6 , 10 – 15 , 24 – 84 . Quantitative analysis of the accuracy of cheiloscopy for sexual dimorphism included seven studies 1 , 5 , 25 , 48 , 49 , 54 , 80 , and 17 studies 10 , 11 , 14 , 28 , 30 , 32 , 34 , 36 , 38 , 42 , 43 , 51 , 56 , 60 , 61 , 63 , 82 were considered in the analyses of the prevalence of lip print patterns (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Barros et al (2006) O dimorfismo sexual é também um fator modificador e responsável pela variabilidade nos padrões de impressão labial entre os estudos. As variações dos tipos de sulco labial entre os sexos masculino e feminino, por vezes proporcionam bases para a identificação humana (Vaishnavi, Sangeetha, & Premavathy, 2019;Yendriwati, Joe & Fitri, 2019). No entanto, no estudo queiloscópico de Prabhu, Dinkar, e Prabhu (2012), não foram observadas diferenças nos padrões labiais femininos e masculinos, visto que o tipo labial predominante em todos os quatro quadrantes avaliados, para ambos os sexos, foi o do tipo V. Da mesma forma, o padrão labial predominante no sexo masculino, foi o mesmo observado para o sexo feminino, no estudo de El Domiaty, Al-Gaidi, Elayat, Safwat, e Galal (2010).…”
Section: Discussionunclassified